Biochemical Analysis of Leaves of some Medicinal Plants of Genus Sesbania - V.B. Kadam2*, R.K. Momin1 and (Journal of Ecobiotechnology, 2011)
The seasonal variation of chlorophyll a, chlorophyll b and carotenoid have been investigated in leaves of Sesbania grandiflora, Sesbania cannabina and Sesbania bispinosa are important medicinal plants. Comparative account of chlorophyll a, chlorophyll b and carotenoid content of leaves of three medicinal plants revealed that, the highest amount of chlorophyll a, chlorophyll b and carotenoidÃ‚Â content in the leaves of Sesbania cannabinaÃ‚Â (3.2 mg/g fresh wt.), (2.76 mg/g fresh wt.) and (1.44 mg/g fresh wt.) in summer seasons.